Association between pan-immune-inflammation value and dyslipidemia in the United States population - Yan, Yu; Jia, Shanshan; Huo, Xingwei; Liu, Lu; Sun, Lirong; Ma, Shuangliang; Chen, Xiaoping (Frontiers in Endocrinology, 2025)
ObjectTo investigate the possible association between pan-immune-inflammation value (PIV) and dyslipidemia.MethodsThis cross-sectional study used the data obtained from National Health and Nutrition Examination Survey (NHANES). The independent variable used the logarithmic form of PIV-log2 (PIV). The definition of dyslipidemia was based on the National Cholesterol Education Program standards. Weighted multivariate logistic regression analyses, the restricted cubic spline (RCS) and threshold effect analysis were explore the association between PIV and dyslipidemia. Stratified analyses were used to identify potential associations with other covariates. The receiver operating characteristic (ROC) curve was constructed compared to systemic immune-inflammation index (SII).Results6,821 participants were included, of whom 47% were male and 77% had dyslipidemia. After adjusting for all confounders, PIV and dyslipidemia had an significantly positive association (OR (95%CI): 1.13 (1.01-1.25); P = 0.03). Compared to participants with lowest quartile (Q1) of PIV, participants with the highest quartile (Q4) had a significantly higher risk of dyslipidemia (OR (95%CI): 1.37 (1.05-1.80); P = 0.022). The RCS curve showed an inverted J-shaped relationship between PIV and dyslipidemia (P-nonlinear = 0.0415, P-overall < 0.001). The threshold effect analysis revealed that the inflection point was 9.192. Stratified analyses showed that age and BMI modified the PIV-dyslipidemia relationship (P for interaction < 0.05). The ROC curve found that compared with SII, PIV had a similar predictive value (area under curve (AUC): 0.566 vs 0.558; P = 0.073).ConclusionThis study discovered that PIV had a significantly positive relationship with dyslipidemia, especially in young and overweight individuals.